Different observation period of exercise training in amyotrophic lateral sclerosis patients: A meta-analysis - Zhou, Baohua; Wei, Jiajun; Zhang, Yanli; Liu, Yue; Shan, Shuhui; Ye, Shan; Li, Baohua; Fan, Dongsheng; Luo, Yongmei (Frontiers in Neurology, 2022)
Objective: The purpose of this meta-analysis was to evaluate the effect of exercise training on the functional ability of patients with amyotrophic lateral sclerosis. Methods: Randomized controlled trials on exercise training in amyotrophic lateral sclerosis patients were retrieved from PubMed, Embase, Web of Science, Cochrane Library and other databases, and meta-analysis was conducted using a fixed effect model or random effect model. Sensitivity analysis was used as a means to study heterogeneity. Results: A total of 8 randomized controlled trials involving 330 patients with amyotrophic lateral sclerosis were included in this study. The results showed that there was statistical significance in the influence of exercise training on amyotrophic lateral sclerosis Functional Rating Scale in the short term (0-4 months) and the medium term (5-8 months) (P < 0.05). There was no significant difference in the effect of the amyotrophic lateral sclerosis Functional Rating Scale-Revised in the short term (0-4 months) or long term (9-12 months) (P ≥ 0.05). In the medium term (5-8 months), there was statistical significance (P < 0.05). There was no significant difference in Forced vital capacity (FVC%) in the short term (0-4 months) (P > 0.05). Conclusion: Exercise training may improve the functional score of amyotrophic lateral sclerosis patients, and more studies should be carried out in the future to verify the effect of exercise training in patients with amyotrophic lateral sclerosis.